Neuronal Polarity Pathways as Central Integrators of Cell-Extrinsic Information During Interactions of Neural Progenitors With Germinal Niches - Solecki, David J. (Frontiers in Molecular Neuroscience, 2022)
Germinal niche interactions and their effect on developing neurons have become the subject of intense investigation. Dissecting the complex interplay of cell-extrinsic and cell-intrinsic factors at the heart of these interactions reveals the critical basic mechanisms of neural development and how it goes awry in pediatric neurologic disorders. A full accounting of how developing neurons navigate their niches to mature and integrate into a developing neural circuit requires a combination of genetic characterization of and physical access to neurons and their supporting cell types plus transformative imaging to determine the cell biological and gene-regulatory responses to niche cues. The mouse cerebellar cortex is a prototypical experimental system meeting all of these criteria. The lessons learned therein have been scaled to other model systems and brain regions to stimulate discoveries of how developing neurons make many developmental decisions. This review focuses on how mouse cerebellar granule neuron progenitors interact with signals in their germinal niche and how that affects the neuronal differentiation and cell polarization programs that underpin lamination of the developing cerebellum. We show how modeling of these mechanisms in other systems has added to the growing evidence of how defective neuronal polarity contributes to developmental disease.